A new chromogranin A–dependent angiogenic switch activated by thrombin - Crippa, Luca; Bianco, Mimma; Colombo, Barbara; Gasparri, Anna M.; Ferrero, Elisabetta; Loh, Y. Peng; Curnis, Flavio; Corti, Angelo (Blood, 2013)
Angiogenesis, the formation of blood vessels from pre-existing vasculature, is regulated by a complex interplay of anti and proangiogenic factors. We found that physiologic levels of circulating chromogranin A (CgA), a protein secreted by the neuroendocrine system, can inhibit angiogenesis in various in vitro and in vivo experimental models. Structure-activity studies showed that a functional anti-angiogenic site is located in the C-terminal region, whereas a latent anti-angiogenic site, activated by cleavage of Q76-K77 bond, is present in the N-terminal domain. Cleavage of CgA by thrombin abrogated its anti-angiogenic activity and generated fragments (lacking the C-terminal region) endowed of potent proangiogenic activity. Hematologic studies showed that biologically relevant levels of forms of full-length CgA and CgA1-76 (anti-angiogenic) and lower levels of fragments lacking the C-terminal region (proangiogenic) are present in circulation in healthy subjects. Blood coagulation caused, in a thrombin-dependent manner, almost complete conversion of CgA into fragments lacking the C-terminal region. These results suggest that the CgA-related circulating polypeptides form a balance of anti and proangiogenic factors tightlyregulated byproteolysis. Thrombin-induced alteration of this balance could provide a novel mechanism for triggering angiogenesis in pathophysiologic conditions characterized by prothrombin activation. •Circulating chromogranin A and its fragments form a balance of anti- and pro-angiogenic factors regulated by thrombin-dependent cleavage.•The alteration of this balance could provide a new mechanism for triggering angiogenesis in cancer and other pathophysiologic conditions.